PEMBELAJARAN MENGANALISIS STRUKTUR DAN KEBAHASAAN TEKS EKSPOSISI DENGAN METODE THINK PAIR AND SHARE UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PADA PESERTA DIDIK KELAS X SMAN 6 BANDUNG TAHUN PELAJARAN 2018/2019 - Nugraha, Eggie; Heriyanto, Ari (STKIP Subang, 2020)
Learning to analyze the structure and linguistic exposition text is part of reading skills by optimizing critical thinking skills. The research results that have been carried out by the authors are: 1) The first hypothesis is accepted. The author gets the average value of learning implementation is 3.65; 2) The second hypothesis is accepted. This can be proven by the results of the experimental class pretest average score of 27.14 and the experimental class posttest value of 82.28; 3) The third hypothesis is accepted. This can be proven based on the results of the t test data, obtained a degree of freedom of 24 with a 95% confidence level and a significant level of 5% with the results of t count> t table. 4) The fourth hypothesis is accepted. The pretest data in the experimental class is a minimum score of 14.29, a maximum score of 42.86, a total value of 678.59 and a mean value of 27.14. Posttest data in the experimental class got a minimum score of 71.43, a maximum score of 92.86, a total value of 2057.11 and a mean value of 82.28. The pretest data in the control class obtained a minimum score of 0, a maximum score of 42.86, a total value of 450 and a mean value of 18. The posttest value of the experimental class with a minimum score of 35.71, a maximum score of 85.71, a total value of 1478.55, and the mean value is 59.14; 5) The fifth hypothesis is accepted. The experimental class gets an average value of 82.28, an average value of 59.14; 6) The sixth hypothesis is accepted. In the experimental class, the average score obtained from the observation sheets of critical thinking skills of students was 25 people including in the good category (B). Based on these data, the authors conclude that analyzing the structure and language of the exposition text with the think pair and share method to improve the critical thinking skills of class X students successfully.